2009
DOI: 10.5713/ajas.2009.80254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Individual, Group or ESF Housing in Pregnancy and Individual or Group Housing in Lactation on Sow Behavior

Abstract: To evaluate the effect of different housing systems on sow behavior, 80 gilts were randomly allocated at puberty to four treatments: i) sow stall in gestation followed by farrowing crate (SC), ii) group housing with individual feeding in gestation followed by farrowing crate (GC), iii) ESF (Electronic Sow Feeding) system in gestation followed by farrowing crate (EC), and iv) ESF system followed by group farrowing pen (EG). Behavioral observations were carried out on a total of 16 animals per treatment at the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…More standing, sitting, rooting, and drinking were also observed in stalled sows than in group-penned sows and sows housed in electronic sow feeding (ESF) system (Weng et al, 2009). The ESF sows had higher time spent for lying and less time spent for rooting and drinking (Weng et al, 2009). This was consistent with the results of Chapinal et al (2010a) indicating more lying in ESF sows than in stalled sows and group-penned sows with trickle feeding system.…”
Section: Table 3 Effects Of Housing On Behavior Of Gestating Sowssupporting
confidence: 71%
See 1 more Smart Citation
“…More standing, sitting, rooting, and drinking were also observed in stalled sows than in group-penned sows and sows housed in electronic sow feeding (ESF) system (Weng et al, 2009). The ESF sows had higher time spent for lying and less time spent for rooting and drinking (Weng et al, 2009). This was consistent with the results of Chapinal et al (2010a) indicating more lying in ESF sows than in stalled sows and group-penned sows with trickle feeding system.…”
Section: Table 3 Effects Of Housing On Behavior Of Gestating Sowssupporting
confidence: 71%
“…• Munsterhjelm et al (2008) found that stalled sows engaged more in standing inactive, which was an indicator of poor welfare, than did group-penned sows. More standing, sitting, rooting, and drinking were also observed in stalled sows than in group-penned sows and sows housed in electronic sow feeding (ESF) system (Weng et al, 2009). The ESF sows had higher time spent for lying and less time spent for rooting and drinking (Weng et al, 2009).…”
Section: Table 3 Effects Of Housing On Behavior Of Gestating Sowsmentioning
confidence: 99%
“…Because group-farrowing systems are designed to accommodate natural behaviors performed by sows during farrowing and lactation, research on group-farrowing systems usually focuses on behavior and performance of sows (Weng et al, 2009;Baxter 'Corresponding author: lhwang2007@sina.com Current address: College of Animal Science and Technology, Qingdao Agricultural University, Qingdao, Shandong, China 266109.…”
Section: Introductionmentioning
confidence: 99%
“…Another thing to consider is that older sows in the FF-pens were likely to have farrowed in crates in their previous parities and did as such not have any experience with the free farrowing system. Previous housing experience can influence sow behaviour during early lactation (Cronin et al, 1996;Weng et al, 2009) and this can also explain why older sows seemed to perform worse than younger sows. Our results also showed that older sows had more stillborn piglets; but this might be linked to the higher number of total born piglets of older sows .…”
Section: Influence Of Parity On Piglet Mortalitymentioning
confidence: 99%